De por qué en la filosofía importan los ejemplos - Fermandois, Eduardo (2008)
“On Why in Philosophy Examples Matter”. The purpose of the article is to show the need of using examples in philosophy, associating to them four functions: to illustrate, explain, argue and show. Among other assertions, we attempt to justify the following: a) Examples are, as well as illustrations, evidences;such that what may be seen as an act of didactic generosity may be considered properly as the response to an always possible demand. b) The introduction of philosophical concepts requires frequently a mutual cooperation between definition and example; the need of the latter in conceptual explanation is condoned by a reflection on the following of rules. c) A certain overrating of the counterexample and underrating of the example are tokens of a notion of philosophy put hereinto question. d) In Wittgenstein and other authors, a little heeded function of some examples is detected: of showing an alternative way of viewing the matter, of re-describing ancient philosophical themes. Towards the end, the issue of theexample is assumed –this time– as an example of a more general issue: that of the relation between rhetoric and philosophy.